Peran Ekstrakurikuler Tari Bulus Tawun dalam Mengembangkan Kepercayaan Diri Anak - Rinda Ayu Ignatyandari; Rela Mar’ati; Azizunnisak Hidayati Wahyuna (Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study aims to analyze the role of the Bulus Tawun Dance extracurricular, a traditional dance from Ngawi, in developing self-confidence in early childhood. The research used a qualitative approach with a case study method at TK Dharma Wanita Rejomulyo 1, Karangjati, Ngawi. Data were collected through participatory observation of five children and in-depth interviews with the principal, accompanying teachers, and the dance creator. The findings reveal that children's participation in this dance extracurricular significantly developed both aspects of self-confidence: outer and inner. This development was not only marked by an increase in courage to perform (outer aspect) but also through the internalization of character values embedded in each dance movement, such as politeness, responsibility, and perseverance (inner aspect). The study concludes that the Bulus Tawun Dance serves as an effective medium. Its effectiveness lies not only in the simplicity of its easily imitated movements but especially in the integration of dance practice with the instillation of philosophical values through storytelling and habituation methods, which are appropriate for early childhood learning characteristics.